The Impact of Voyage Quality and Customer Experience Management on Customer Satisfaction: A Case Study of Pelindo III Tanjung Emas Port, Semarang - Sagitha Setya, Ulung Tri; Adeyanto, Brahma; Prabowo, Bosin; Multazam, Akhmad Gifari; Kakisina, Girnis; Ahadianto, Muhammad Sayakfika (Meteor STIP Marunda, 2024)
Ports are integral to global trade and economic development, serving as essential hubs for maritime transport and logistics. This study explores the impact of voyage quality and customer experience management on customer satisfaction at Pelindo III Tanjung Emas Port, Semarang. Employing a structured analytical approach, the research examines critical factors such as service quality, administrative efficiency, technological support, and customer communication. Data from port users reveal significant challenges, including delays, fluctuating container traffic, and gaps in proactive communication, which adversely affect satisfaction levels. The findings demonstrate that voyage quality and customer experience management significantly influence customer satisfaction, both independently and in combination. By addressing administrative delays, enhancing technology-driven solutions, and fostering clear communication, the port can improve operational efficiency and user satisfaction. These insights underscore the importance of integrating service quality with customer-centric strategies to drive competitiveness and sustainability in the maritime industry.